Criminological Characteristics and Prevention of Organized Crime - Tuychiboev Sodikjon Saburovich (Genius Journals, 2023)
This article is a criminological analytical work devoted to the study of organized crime. The authors carry out a detailed analysis and characterization of organized crime, exploring its main causes, structure and methods of activity. The article deals with various types of organized crime, including mafia groups, drug cartels, gangs and terrorist organizations. The authors analyze the motivation and goals of these criminal groups, explore their impact on society and the economy, and analyze the mechanisms of organization and functioning of such criminal structures. Particular attention is paid to the prevention of organized crime in the article. The authors offer various strategies and approaches to combating organized crime at various levels - from state to local. The article discusses measures aimed at the elimination and weakening of criminal structures, including law enforcement operations, international cooperation and social rehabilitation measures. In conclusion, the authors of the article emphasize the importance of an integrated approach to the problem of organized crime. They call for the joint efforts of law enforcement agencies, government institutions, public organizations and citizens in general to counter organized crime and ensure security and stability in society.
Keywords: Organized crime; Criminology; Crime prevention